Prevalence of Intimate Partner Violence among Iranian Women: A Systematic Review and Metaanalysis from 2010-2020 - Ali Ameli; Alireza Salehi; Hossein Molavi Vardanjani; Mina Vojoud Vojoud; Firoozeh Rahmati (Shiraz University of Medical Sciences, 2024)
Background: Intimate partner violence (IPV) is a significant public health issue, especially in developing countries. This study aimed to provide a systematic review and meta-analysis of IPV among married Iranian women.Methods: In this systematic review and meta-analysis, following PRISMA guidelines, eight electronic databases were searched for quantitative articles, with the target population of married Iranian women. Articles from 2010 to 2020 were extracted and assessed with an 8-scored checklist for risk of bias. Different types of IPV include mental, physical, and sexual types. Heterogeneity was assessed with I2 and Q tests. Random effect model was used for meta-analysis. Factors such as income, education, employment, mean age, urbanization, and human development index (HDI) were assessed within homogenous groups.Results: Thirty-four studies (19,445 participants) were included. The mean age of women was 33.4 years. The overall prevalence of past-year IPV was estimated at 62.6% (CI: 53.6-71.5). Mental, physical, and sexual violence were estimated at 59% (CI: 53.7- 64.4), 30.8% (CI: 26.2-35.4), and 29% (CI: 22.4-35.5), respectively. The results revealed that a negative correlation existed between the occurrence of violence and higher education, higher HDI indices for regions, and employment.Conclusion: The findings of this study indicate that IPV exists in high proportions in Iran. Improving the economic situation, increasing education, and raising public awareness through social media are the preventive factors.